2018
DOI: 10.3390/ijerph15050847
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vaccination as an Essential Component of Life-Course Immunization and Its Contribution to Preventive Neonatology

Abstract: Maternal immunisation schedules are increasingly coming under the spotlight as part of the development of lifetime immunisation programmes for the role that they play in improving maternal, foetal, and neonatal health. Maternally-acquired antibodies are critical in protecting infants during the first months of their lives. Maternal immunisation was previously overlooked owing to concerns regarding vaccinations in this untested and high-risk population but is now acknowledged for its potential impact on the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
0
35
0
1
Order By: Relevance
“…This paper shares HCP insights on LCI which we see as an important addition to available evidence, since such survey data are seldom published besides the live interaction [12,19,20]. Furthermore, pedagogical tools such as ARS have demonstrated value by facilitating active learning and 'sense making' through real-time insights, hence supporting our rationale for administering an ARS-based survey [7,21].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This paper shares HCP insights on LCI which we see as an important addition to available evidence, since such survey data are seldom published besides the live interaction [12,19,20]. Furthermore, pedagogical tools such as ARS have demonstrated value by facilitating active learning and 'sense making' through real-time insights, hence supporting our rationale for administering an ARS-based survey [7,21].…”
Section: Discussionmentioning
confidence: 69%
“…Maternal immunization is the only immunization strategy that directly benefits two generations through a single preventive intervention. Still, the worldwide implementation of maternal immunization has remained suboptimal [7]. Furthermore, the WHO also recommends routine immunization for healthy adolescents (e.g., human papillomavirus vaccine for adolescents) and adults (e.g., seasonal influenza vaccine), timely receipt of the booster dose (e.g., tetanus toxoid, reduced diphtheria toxoid and acellular pertussis [Tdap] and meningitis) and catch-up vaccinations if routine immunization during childhood was missed (e.g., the measles, mumps, rubella or varicella vaccine) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, vaccine development against cytomegalovirus (CMV) is also proceeding with potential use of the vaccine both before and during pregnancy to benefit both mother and neonate. CMV infection is a major public health priority which causes substantial long-term morbidity, particularly sensorineural hearing loss in newborns [77]. Up until now, progress towards the development of a CMV vaccine has been limited due to an incomplete understanding of the correlates of protective immunity for the fetus.…”
Section: Maternal Vaccination Recommendations For Future Vaccinesmentioning
confidence: 99%
“…During their antenatal visits, mothers have their vaccination records assessed and are vaccinated where necessary. Maternal vaccination is the only time that vaccination can benefit two generations from a single input, with the possible exception of live polio vaccine [82]. A study in Beijing found that the seroprevalence of maternal and cord antibodies specific for diphtheria, tetanus, pertussis, measles, mumps, and rubella were lower than expected and the authors recommended a vaccination program before pregnancy [83].…”
Section: Maternal Vaccinationmentioning
confidence: 99%